REVITALIZATION OF MINAHASAN CULTURE THROUGH VOCABULARY OF TRADITIONAL FOOD NAMES IN THE CONTEXT OF DEVELOPING CULINARY TOURISM IN NORTH SULAWESI PROVINCE - Rina P Pamantung; Victorien C G Katuuk; Julaiha Kyai Modjo (LPPM Institut Pendidikan Nusantara Global, 2023)
The research on Revitalization of Minahasan Culture Through Vocabulary of Traditional Food Names in The Context of Developing Culinary Tourism in North Sulawesi Province intends to improve previous research that has been conducted. This research is proposed for one year. The problem formulated in this research is the naming system of Minahasan traditional food and its meaning. This research aims to (1) identify and classify the naming system of traditional Minahasan food, (2) analyze and describe the meaning of traditional Minahasan food names. The specific targets to be achieved in this research are (1) the identification and classification of the naming system of traditional Minahasan food , (2) the identification and classification of linguistic units in the form of words, phrases, and clauses of traditional Minahasan food names, and (3) the results of explanation and description in the form of cultural meaning in linguistic units in the form of words, phrases, and clauses of traditional Minahasan food names. The vocabulary of traditional Minahasan food names as a naming system that has meaning and cultural value based on the cognition of the Minahasan community was found in this study. The origin of food names and the concept of Minahasan culture are also reflected in traditional Minahasan food names. The method used is descriptive qualitative method with an approach through ethnography, synchronic linguistics and gastronomic linguistics methods. Techniques and data collection were observation and interview. The research location is in North Sulawesi Province, especially Minahasan Regency by selecting several cities in the area of North Sulawesi Province by purposive sampling, namely data collection according to research needs. The results of the research are food labeled linulut (food that is inserted in bamboo and burned) and non-linulut (food not in bamboo). The naming system of traditional Minahasann food consists of ingredients, cooking utensils, food makers, places where food is made, the arrival of Minahasann people, and people's names. The form of traditional Minahasann food names consists of words, phrases, and clauses. Pangi, gohu and woku are words. Woku blanga, rica rodo, and Sayor pa'it are phrases. Clauses consist of Ayang woku isi di bulu, Babi woku isi di bulu, and ikang mas bungkus deng daong woka. The meaning of food names is denotative meaning and connotative meaning. The denotative meaning corresponds to the food ingredient, namely pangi. The connotative meaning is the name of the food sende'en, pongkor, fried brot cookies, and Bobengka.